Preface to the Special Issue “Ecologically sustainable fishing”: Project KESKALA background, objectives and conclusions - Lehtonen, Hannu; Estlander, Satu; Horppila, Jukka; Nurminen, Leena; Olin, Mikko; Rask, Martti; Ruuhijärvi, Jukka; Tiainen, Joni
2017